Transcystic draingge after choledochoduodenostomy - Benedek, Pedro; Estable, Miguel A; Rodríguez Juanotena, Jorge (Cirugía del Uruguay, 1977)
The authors point out the suitable use of drainage trough the cystic dut. By means of this drainage one can control: a) anastomosis, b) hepatocholedochus, c) and besides, to perform a lavage. A clinical case is shown where one followed this method which allowed to acknowledge three residual stones; they pass by means of a lavage.